2004
DOI: 10.1679/aohc.67.149
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and immunohistochemical changes to thymic epithelial cells in the irradiated and recovering rat thymus

Abstract: The present study analyzed morphological and immunohistochemical changes of thymic epithelial cells in the irradiated and recovering rat thymus. Observations showed the number of thymocytes was initially severely reduced after irradiation but abruptly increased on days 3 to 5 after 6 Gy and on days 7 to 11 after 8 Gy irradiation. To analyse the mechanisms for this abrupt recovery of the thymocytes after irradiation, the expression of p63 in the normal and irradiated thymus was immunohistochemically studied as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Because of the general alterations of the Aire-deficient medullary compartment described here and previously (20), we evaluated the impact of Aire deficiency on p63 expression by TE, reasoning that Aire could affect other pathways regulating MTEC differentiation. As shown in Figure 4, and in agreement with previous reports (3538), p63 expression was widespread among epithelial cells in cortical and medullary compartments, with a higher density of p63 + cells in the medulla (Figure 4a). Within the medullary compartment, there was little overlap between p63 expression and either Aire or high levels of K8 (Figure 4b & c).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Because of the general alterations of the Aire-deficient medullary compartment described here and previously (20), we evaluated the impact of Aire deficiency on p63 expression by TE, reasoning that Aire could affect other pathways regulating MTEC differentiation. As shown in Figure 4, and in agreement with previous reports (3538), p63 expression was widespread among epithelial cells in cortical and medullary compartments, with a higher density of p63 + cells in the medulla (Figure 4a). Within the medullary compartment, there was little overlap between p63 expression and either Aire or high levels of K8 (Figure 4b & c).…”
Section: Resultssupporting
confidence: 92%
“…The impact of p63-deficiency on thymic epithelium indicates that p63 contributes to the maintenance and/or behavior of TE at proximal stages of their differentiation (8, 9). Although there are indications that p63 expression identifies progenitor epithelial cells (15), the extensive expression of p63 by thymic epithelial cells (3538); this report) indicates that p63 expression in the thymus is not restricted to this relatively rare population (4) and includes transit amplifying cells as well. There is debate regarding the role of p63 in epithelial differentiation, where it has been implicated in differentiation, cell fate specification, proliferation, survival, senescence, apoptosis, cell-cell and cell-matrix interaction programs (reviewed in (13, 16, 45)).…”
Section: Discussionmentioning
confidence: 67%
“…P63 deficient mice exhibit a severely hypoplastic non-functional thymus [59], [60] and appears to show the effect in early TECs development. P63 expression has been reported to identify epithelial stem cells [84] however, the abundance of p63-expressing cells in the thymus (Figure 8 & [79], [85], [86], [87], [88]) and other tissues like bladder epithelium indicates that p63 expression is maintained in the immediate progeny of the stem cells as well. In the skin, p63 expression is associated with K14 + progenitor cells in the basal layer and is lost as the cells lose proliferative potential and differentiate [62].…”
Section: Discussionmentioning
confidence: 95%
“…With these cytotoxic therapies, the total thymus anlage is decreased, raising the likelihood that immunohistochemical studies may be subject to variations in the size and depth of sections examined. Using this technique, while studies concur that thymocytes are more radiosensitive than TEC, 37–39 assessments of TEC alterations after radiation have differed. Some have suggested that the major effects may occur in the medulla with selective depletion of UEA+ medullary TEC 40,41 and medullary dendritic cells 42 .…”
Section: Introductionmentioning
confidence: 99%